Phlpp1 facilitates post-traumatic osteoarthritis and is induced by inflammation and promoter demethylation in human osteoarthritis. Issue 6 (June 2016) - Bradley, E.W.; Carpio, L.R.; McGee-Lawrence, M.E.; Castillejo Becerra, C.; Amanatullah, D.F.; Ta, L.E.; Otero, M.; Goldring, M.B.; Kakar, S.; Westendorf, J.J.
Summary: Objective: Osteoarthritis (OA) is the most common form of arthritis and a leading cause of disability. OA is characterized by articular chondrocyte deterioration, subchondral bone changes and debilitating pain. One strategy to promote cartilage regeneration and repair is to accelerate proliferation and matrix production of articular chondrocytes. We previously reported that the protein phosphatase Phlpp1 controls chondrocyte differentiation by regulating the activities of anabolic kinases. Here we examined the role of Phlpp1 in OA progression in a murine model. We also assessed PHLPP1 expression and promoter methylation. Design: Knee joints of WT and Phlpp1 −/− mice were surgically destabilized by transection of the medial meniscal ligament (DMM). Mice were assessed for signs of OA progression via radiographic and histological analyses, and pain assessment for mechanical hypersensitivity using the von Frey assay. Methylation of the PHLPP1 promoter and PHLPP1 expression were evaluated in human articular cartilage and chondrocyte cell lines. Results: Following DMM surgeries, Phlpp1 deficient mice showed fewer signs of OA and cartilage degeneration. Mechanical allodynia associated with DMM surgeries was also attenuated in Phlpp1 −/− mice. PHLPP1 was highly expressed in human articular cartilage from OA patients, but was undetectable in cartilage specimens from femoral neck fractures (FNFxs). Higher PHLPP1 levels correlated with less PHLPP1 promoter CpG methylation in cartilage from OA patients. Blocking cytosine methylation or treatment with inflammatory mediators enhanced PHLPP1 expression in human chondrocyte cell lines. Conclusion: Phlpp1 deficiency protects against OA progression while CpG demethylation and inflammatory cytokines promote PHLPP1 expression.